THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE COMMITMENT THROUGH WORK CULTURE AT EMPLOYEES OF PT. PLN (PERSERO) CUSTOMER SERVICE IMPLEMENTING UNIT (UP3) PALU - Pratiwi Munthe, Julyandani; Natsir, Syahir; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aimed to determine the influence of work discipline on organizational commitment through work culture at PT. PLN (Persero) Executive Customer Service Management Unit Palu. This was a correlational research. The research sample was all employees at PT. PLN (PERSERO) Executive Customer Service Management Unit Palu with 154 employees. This research used the Structural Equation Modelling (SEM) method, which is operated by SMART-PLS. The results of this research indicate that 1) Work discipline has a significant influence on employee commitment at PT. PLN (PERSERO) Executive Customer Service Management Unit Palu, 2) Work discipline has a significant influence on work culture at PT. PLN (PERSERO) Executive Customer Service Management Unit Palu, 3) Work culture has a significant influence on employee commitment to PT. PLN (PERSERO) Executive Customer Service Management Unit Palu, 4) Work discipline influence employee commitment mediated by work culture at PT. PLN (PERSERO) Executive Customer Service Management Unit Palu. Keywords: Work Discipline, Employee Commitment, Work Culture.